2014
DOI: 10.1039/c4nr01826e
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-doped upconversion nanoparticles electrostatically coupled with photosensitizers for near-infrared-triggered photodynamic therapy

Abstract: Lanthanide-doped upconversion nanoparticles (UCNPs) have recently shown great promise in photodynamic therapy (PDT). Herein, we report a facile strategy to fabricate an efficient NIR-triggered PDT system based on LiYF4:Yb/Er UCNPs coupled with a photosensitizer of a β-carboxyphthalocyanine zinc (ZnPc-COOH) molecule via direct electrostatic interaction. Due to the close proximity between UCNPs and ZnPc-COOH, we achieved a high energy transfer efficiency of 96.3% from UCNPs to ZnPc-COOH, which facilitates a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 53 publications
1
86
0
Order By: Relevance
“…UCNPs-based PDT agent for the inhibition of tumor growth both in vitro and in vivo due to high energy transfer efficiency [42]. Although LiREF 4 (RE = Y, Er-Lu) UCNPs have been widely reported, a systematic survey on the optical and magnetic properties of LiGdF 4 nanoparticles is still lacking because the syntheses of tetragonal-phase LiGdF 4 UCNPs via wet chemical method is challenging [31,43,44] and instead, orthorhombic-phase GdF 3 is apt to be formed (Fig.…”
Section: :Ybermentioning
confidence: 99%
See 1 more Smart Citation
“…UCNPs-based PDT agent for the inhibition of tumor growth both in vitro and in vivo due to high energy transfer efficiency [42]. Although LiREF 4 (RE = Y, Er-Lu) UCNPs have been widely reported, a systematic survey on the optical and magnetic properties of LiGdF 4 nanoparticles is still lacking because the syntheses of tetragonal-phase LiGdF 4 UCNPs via wet chemical method is challenging [31,43,44] and instead, orthorhombic-phase GdF 3 is apt to be formed (Fig.…”
Section: :Ybermentioning
confidence: 99%
“…material is an outstanding host matrix for both upconversion (UC) and down-conversion (DC) luminescence [38][39][40][41][42]. Mahalingam et al reported that their synthesized Yb and Tm codoped LiYF 4 UCNPs not only exhibit intense UC emission under excitation at 980 nm, but also generate additional emission lines in the deep-UV (294 nm) and near-infrared regions (1.46 µm), which can be used for anti-counterfeiting and telecommunication applications, respectively [38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In view of this, Chen and Wang [105] attached β-carboxyphthalocyanine zinc (ZnPc(COOH), absorption peak at *676 nm) directly to ligand-free LiYF 4 :Yb/Er UCNPs in a very recent report. Owing to the removal of surface oleate ligands by acid treatment, positively charged Ln 3+ ions were exposed on the surface of UCNPs, which was confirmed by a positive zeta potential of +49.5 mV.…”
Section: Direct Conjugation Via Non-covalent Interactionsmentioning
confidence: 98%
“…For example, based on a high‐temperature coprecipitation method, a series of AREF 4 (A = Li, Na, K; RE = Eu, Sm, Gd, Y, Lu, et al) NPs with different crystalline phases and particle sizes ranging from several to hundreds of nm were synthesized ( Figures 2 a–c) 15. Through a modified thermal decomposition method, ultrasmall (<5 nm) cubic LaOF, orthorhombic Lu 6 O 5 F 8 , and tetragonal YOF NPs were fabricated (Figures 2d–f) 16.…”
Section: General Protocols For the Fabrication Of Inorganic Lanthanidmentioning
confidence: 99%